Optimasi Media Sosial Instagram Disdukcapil Sidoarjo Sebagai Upaya Peningkatan Kualitas Pelayanan Publik - Hanifah, Fauzziyah; Dzuhrina, Isnani (Jurnal Pustaka Komunikasi, 2024)
The emergence of social media and its development makes it easier for individuals to carry out various interactions. Social Media plays a role as an effort to improve the quality of public services. Social media is a more efficient means of building relationships between government agencies and the community. One of them can lead to achieving understanding between the community and government agencies because this is an effort to improve the quality of public services. One of the efforts made by the Sidoarjo Dukcapil Department to improve the quality of public services is by optimizing Instagram social media. Optimizing Instagram in government agencies is something that needs attention, both in sharing information and activity content. Therefore, this research aims to find out how to optimize the Sidoarjo Disdukcapil Instagram social media as an effort to improve the quality of public services based on the 4C concept and The Circular Model of Some for Social Communication, using a qualitative descriptive approach. The results of this research show that the Sidoarjo Disdukcapil Instagram social media optimization as an effort to improve the quality of public services still does not fully fulfill the dimensions contained in the theory of social media utilization, namely Context, Communication, Collaboration, and Connection. This is because a conducive communication space has not been created and social media managers have not responded to all responses from the public, besides that the collaboration carried out has not been extensive. So there are still many dimensions that still need to be improved.